Treatment with low-dose tyrosine kinase inhibitors due to significant haematologic toxicity in patients with CML with prolonged treatment failure prevents haematologic progression - Vráblová, Lucia; Klamová, Hana; Skoumalová, Ivana; Navrátilová, Jana; Janská, Romana; Grohmann, Jan; Holzerová, Milena; Faber, Edgar (Hematology, transfusion and cell therapy, 2024)
BACKGROUND: A lower dosage of tyrosine kinase inhibitors (TKIs) in patients with chronic myeloid leukaemia (CML) has shown efficacy in managing short-term toxicity and maintaining a deep molecular response in patients who fail to achieve treatment-free remission. METHOD: From over 700 patients with CML who were treated at two centres over the last three decades, this retrospective study identified eight patients characterised by long-term treatment failure and simultaneous prolonged significant haematologic toxicity that prevented the use of the standard tyrosine kinase inhibitor dosage. RESULTS: Patients had a high or intermediate ELTS risk score, and most had significant comorbidities. Two patients were treated previously with busulfan, and four were aged over 70, which might explain the reduced pool of normal haematopoietic stem cells. However, concomitant myelodysplastic syndrome or the presence of clonal haematopoiesis of indeterminate potential was not demonstrated. Despite prolonged treatment failure, the survival of these patients (who were ineligible for stem cell transplantation) ranged from 45-396 months. Neither mutations in the ABL kinase domain nor additional cytogenetic abnormalities developed during the treatment of these patients, prompting speculation about the low selective pressure of low-dose tyrosine kinase inhibitors and/or the absence of mutations at diagnosis. CONCLUSION: It is important not to stop treatment with tyrosine kinase inhibitors at a low personalised dosage in CML patients with prolonged significant haematologic toxicity despite long-term treatment failure.
Keywords: Chronic myeloid leukaemia; Tyrosine kinase inhibitor; Low dosage; Intermittent dosage; Kinase domain mutation; Haematologic toxicity